2023
DOI: 10.31234/osf.io/5y83h
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How can we measure metacognition in creative problem-solving? Standardization of the MCPS scale

Abstract: Creative problem-solving is associated with the resolution of ill-defined tasks where the goals, procedure, and evaluation criteria are not predetermined. Successful problem solvers have to set their own unique goals, develop appropriate strategies, plan individual steps, generate various possible solutions, monitor and regulate the problem-solving process, and evaluate the outcome for novelty and usefulness. The present study aims to standardize the Metacognition in Creative Problem-Solving (MCPS) scale, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…However, few studies have speci cally examined the affordances of conversational agents like ChatGPT for developing metacognition and self-regulation. Urban et al (2023) argue that current large language models like ChatGPT lack the capabilities to promote metacognitive awareness or engage students in truly selfdirected learning. Their experimental ndings revealed that when interacting with ChatGPT, students demonstrate poorer comprehension monitoring and evaluation of responses compared to learning from a human tutor.…”
Section: Chatgpt In Educationmentioning
confidence: 99%
“…However, few studies have speci cally examined the affordances of conversational agents like ChatGPT for developing metacognition and self-regulation. Urban et al (2023) argue that current large language models like ChatGPT lack the capabilities to promote metacognitive awareness or engage students in truly selfdirected learning. Their experimental ndings revealed that when interacting with ChatGPT, students demonstrate poorer comprehension monitoring and evaluation of responses compared to learning from a human tutor.…”
Section: Chatgpt In Educationmentioning
confidence: 99%
“…While traditional teaching methods endure, the infusion of AI-driven platforms presents innovative pedagogical pathways, promising to augment students' cognitive capabilities. Leveraging empirical data and statistical analyses, this research aims to unveil the multifaceted influence of varied stakeholders' engagement with ChatGPT [3]. By examining correlations between these interactions and the enhancement of critical thinking, problem-solving, and creativity, this study seeks to elucidate the pedagogical advantages of AI-based educational tools.…”
Section: Introductionmentioning
confidence: 99%